Plexiform neurofibroma in peripheral neurofibromatosis. - Milano, A. (European Journal of Pediatric Dermatology, 2013)
Plexiform neurofibromas, that is those neurofibromas which affect more nerves at the same time, are charaterized by elongated shape and among the neurofibromas of peripheral neurofibromatosis are the earliest to appear, being often present in the first decade of life.